Unique Fixed Point Results and Its Applications in Complex-Valued Fuzzy b-Metric Spaces. (1st September 2022) - Humaira,; Sarwar, Muhammad; Mlaiki, Nabil
Abstract : The goal of this paper is to extend the concept of complex-valued fuzzy metric space to complex-valued fuzzy b -metric spaces and to discuss various existence results for fixed points to ensure their existence and uniqueness. To demonstrate the viability of the proposed strategies, a nontrivial example is used. Finally, applications to integral equations and initial value problems in mechanical engineering are discussed to demonstrate the superiority of the obtained results.